CARRYING CAPACITY OF NON-RICE FEATURED CROPS FOR ALTERNATIVE FOOD AVAILABILITY IN BANGGAI REGENCY, CENTRAL SULAWESI - Hidayat Arismunandar Katili; Ruslan A. Zaenuddin; Regita Cahyani; Sariani Sariani; Dian Puspapratiwi (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2023)
Basic human needs are something that is needed by man to maintain his life, and the carrying capacity of food crops is very important for food availability in the face of food crises in each region. The purpose of this study is to find out which non-rice food crops are superior and the carrying capacity of non-rice superior food crops that can be used as alternative food in Banggai Regency. The data used in this research is data on the production of non-rice food crops in 2017 and 2021. Furthermore, the research was conducted using qualitative methods that were analyzed descriptively quantitatively with the LQ-SSA approach and the Carrying Capacity of Agricultural Area Land. So that the results of the analysis of LQ and SSA of non-rice food crops that are superior are obtained, namely corn which is spread in 14 districts, sweet potatoes in 5 districts, peanuts in 4 districts, and soybeans in 1 district. Furthermore, the land carrying capacity of non-rice superior food crops, obtained the results of corn, sweet potato, peanut, and soybean plants experiencing a surplus (SL>DL), which means that these superior food crops can contribute to a decent life for the population and determine the carrying capacity of the agricultural area of food crops. non-rice seed, the result is corn (ℓ > 1), which means that corn can be used as an alternative food to replace rice. As well as for Sweet Potato, Peanut, and Soybean plants, the results obtained (ℓ < 1), which means that these plants cannot be used as an alternative food to replace rice in Banggai Regency.